Amplification of 3q26 and 5p15 regions in cervical intraepithelial neoplasia. (17th September 2014) - Kudela, Erik; Farkasova, Anna; Visnovsky, Jozef; Balharek, Tomas; Sumichrastova, Petra; Sivakova, Jana; Plank, Lukas; Danko, Jan
Abstract Objective To analyze different amplification patterns of 3q26 and 5p15 regions in low‐grade and high‐grade cervical intraepithelial neoplasia. Design Experimental research. Setting Department of Obstetrics and Gynecology at a medical faculty in Slovakia. Population A group of 83 patients referred for colposcopic examination. Methods Amplification of 3q26 and 5p15 regions was analyzed on the 100 most atypical cells from a cervical cytology slide by fluorescent in situ hybridization using a multicolor hybridization probe. Chi‐squared and Man–Whitney U‐tests were used for statistical analysis. Main outcome measures Liquid‐based cytology samples and biopsy samples obtained during colposcopic examination correlated with high‐risk human papillomavirus status and with amplification patterns of selected regions analyzed by fluorescent in situ hybridization. Results The number of cells with 3q26 and 5p15 gain rises with the severity of the lesion p < 0.01. The sensitivity of 3q26 amplification for CIN2+ lesions was 72.1% (95% confidence interval 56.3–84.7) and specificity was 90.0% (95% confidence interval 76.3–97.1). The sensitivity of 5p15 amplification for CIN2+ lesions was 69.8% (95% confidence interval 53.9–82.8) and specificity was 85.0% (95% confidence interval 70.2–94.3). Conclusion Evaluation of telomerase components can help in differential diagnosis of low‐grade and high‐grade cervical lesions and in individualized management of these patients.